Urban Agriculture - Samer, Mohamed (IntechOpen, 2016)
This book provides useful information about Urban Agriculture, which includes the production of crops in small to large lots, vertical production on walls, windows (window farms), rooftops (green roofs), urban gardens, farmer's markets, economic models of urban gardening, peri-urban agricultural systems, and spatial planning and evolution of the land uses. Additionally, this book elucidates further agricultural technologies, such as the aquaculture systems.